(3GdOYhI Edi JQHjI GdaJjGJ hJYdjegqf Hjf fgVJjf hQGFOJjf (B: (3cQjSJjf Oh HjRGf hej RjGOI (B: (3COH ebGQfs - (3RjGOI, eqj LhQLs ((3HjQhJs (3LGeYI GdQhM GdbOS (B- (3GdcSdjc (B((3dHfGf(B) - (3cdjI GdCOGHs, 2012)
(3Jdbj gPg GdOQGSI GdVhA Ydi ef jeKd YUQj GdfgVI ef NdGd GdCOjHJjf cQjSJjf Oh HjRGf aj GdZQH, heqj RjGOI aj GdTQb(B. (3hPdc ef NdGd JbOje OQGSI JGQjNjI Yf ehdO cQjSJjf Oh HjRGf hfTCJgG, hef Ke OQGSI TNUjJgG, hOQGSI JGQjNjI Yf ehdO eqj RjGOI hfTCJgG hOQGSI TNUjJgG hPdc HgOa EHQGR eG gh eNJda heG gh eDJda Ydi UYjO GdMjGI GdNGUI hGdTNUjJjf(B. (3ceG Jqe GdJQcjR Ydi GdBKGQ GdCOHjI dgGJjf GdQGFOJjf aj GdCOH haj GdJMQjQ GdfSGFj, aJe YQV eDdaGJ cQjSJjf hCacGQgG hJHjGf QSGdJgG ef NdGd eDdaGJgG, ef Ke YQV fXQI ej RjGOI ef NdGd eDdaGJgG hGdQSGdI GdJj CQGOJ EjUGdgG, hPdc ddJhUd Edi ebGQfI JMdjdjI dEHQGR ChLg GdGNJdGa ceG ChLg GdGFJdGa HjfgeG, hGdJj JHjf CqfgG YOjOI aj cdJG GdebGQfJjf, fXQG dJHGYO GdYUQjf JGQjNjG hdGNJdGa GdCMhGd GdTNUjI YfO GdCOjHJjf, hGdCge GNJdGa hVY GdeQCI GLJeGYjG, hMJi GdWQGFb hGdCSGdjH GdCOHjI(B. (3EfeG hLhO GdehVhY GdCHQR GdPj gh GdYfGjI HTDhf GdeQCI hTLhfgG ef NdGd eMGQHI GdLgd aj LejY CfhGYg hCTcGdg gh GdehVhY GdPj cqhf LGeYG egeG aj COH gGJjf GdQGFOJjf(B. (3ceG JWqQbJ GdOQGSI aj ehVY BNQ, Edi eOi JCKjQ CacGQ gGJjf GdCOjHJjf Ydi ef dMbgeG ef COHGA, hef fMG fMhgeG aj GdeWGdHI HGdJYdje YfO GdaJjGJ, eY GdJQcjR Ydi GdaJGI GdYQHjI GdJj eG JRGd JYGfj aj HYV GdHdOGf hJaJbQ Edi CHSW GdMbhb GdeOfjI, hYf hVY GdJYdje YGeI, hJYdje GdaJjGJ NGUI aj dHfGf(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: (3ej RjGOIs; (3GdGfGKs